Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Yang Dimediasi Oleh Produktivitas Kerja Perusahaan CV. Laut Selatan Jaya Di Bandar Lampung - Hepiana Patmarina; Nuria Erisna (Universitas Bandar Lampung (UBL), 2012)
CV. Laut Selatan Jaya engaged in product distributor PT. Mandom Indonesia Tbk face the problem of lack of work discipline shown by the high employee absenteeism and declining productivity of employees that may affect the company's performance. The research problem is: Is employee discipline affect the performance of the company, whether the employee productivity affect the performance of the company, and whether the employee disciplinary effect on labor productivity in CV. Laut Selatan Jaya. The purpose of this study was to determine the effect of employee discipline on company performance, employee productivity effect on corporate performance, and employee discipline effect on labor productivity in CV. Laut Selatan Jaya. Based on the results of quantitative analysis with multiple regression models obtained by the equation: Y = 32,195 + 0.0000001831 0.000000090926 X1 + X2. From these equations it can be seen working discipline coefficient (b1) and employee productivity coefficient (b2) is relatively small. This suggests that the effect of labor discipline and productivity of employees on company performance mediocre. Product Moment Correlation calculation results obtained r1 = 0.08 and r2 = 0.06 means that the discipline of work and employee productivity has positive influence to company performance. The results of the calculation of the coefficient determinant of labor discipline by 64% which means that the influence of labor discipline on corporate performance by 64% and the effect on the performance of the employee's productivity to company performance by 34%. Thus the hypothesis which states that: employee discipline effect on company performance, employee productivity affect the company's performance, and employee discipline effect on labor productivity in CV. South Sea Jaya in Bandar Lampung, is acceptable